The effects of privatization on R&D investments and patent productivity - Federico Munari; Maurizio Sobrero (Fondazione Eni Enrico Mattei (FEEM), 2002)
Over the last two decades privatization programs in different countries radically reduced the role of the State as a key player in the economic arena. We use agency theory to discuss the theoretical relationship between changes in the firm's principal-agent structure following privatization, and incentives to invest in R&D and to patent. We compare the pre and post privatization R&D effort and patenting behavior of 35 companies that were fully or partially privatized in 9 European countries through public share offering between 1980 and 1997. Results show that, after controlling for inter-industry differences, privatization processes negatively affect different measures of R&D commitment. Moreover, the shift from public to private ownership leads to a significant increase in the quantity of patents granted and in their quality, measured by citations' intensity.
Keywords: G34; O32; 330; Privatization; R&D investments; patents; inventions; Privatisierung; Industrielle Forschung; Patent; Prinzipal-Agent-Theorie; Innovation; Eigentümerstruktur; Schätzung; EU-Staaten